The effect of carbohydrates and osmoticum on storage reserve accumulation and germination of Norway spruce somatic embryos. Issue 2 (25th March 2013) - Businge, Edward; Bygdell, Joakim; Wingsle, Gunnar; Moritz, Thomas; Egertsdotter, Ulrika
<x xml:space="preserve">Abstract</x> Somatic embryogenesis (SE) represents a useful experimental system for studying the regulatory mechanisms of embryo development. In this study, the effect of carbohydrates and osmoticum on storage reserve accumulation and germination of Norway spruce [Picea abies (L.) Karst] somatic embryos were investigated. Using time lapse photography, we monitored development from proliferation of proembryogenic masses (PEMs) to maturation of somatic embryos in two P. abies cell lines cultured on two maturation treatments. A combination of sugar assays, metabolic and proteomic analyses were used to quantify storage reserves in the mature somatic embryos. The maturation treatment containing a nonpermeating osmoticum, polyethylene glycol (PEG, 7.5%) and maltose (3%) as the carbohydrate gave significantly high maturation and low germination frequencies of somatic embryos compared to the treatment with only 3% sucrose. Somatic embryos treated with 3% sucrose contained high levels of sucrose, raffinose and late embryogenesis abundant (LEA) proteins. These compounds are known to be involved in the acquisition of desiccation tolerance during seed development and maturation. In addition the sucrose treatment significantly increased the content of starch in the somatic embryos while the maltose and PEG treatment resulted in somatic embryos with a high content of storage proteins. The high levels of sucrose, raffinose and LEA proteins in the embryos treated with 3% sucrose suggest that sucrose may improve the germination of somatic embryos by promoting the acquisition of desiccation tolerance.